A Comparative Analysis of Pomodoro and Time-Blocking in Enhancing Reading Comprehension: Basis for a Reading Toolkit for Teachers - Cristine Joy Hacildo; Jeffrey Astillero (Researchparks Publishing, 2026)
The research study investigated how effective two-time management techniques the Pomodoro Technique and Time-Blocking Method worked to improve first-year English major students reading comprehension skills. The study investigated how pre-test and post-test reading comprehension scores showed different results for participants while assessing which time management method worked better between the two tested methods. The study used a quasi-experimental research design which involved two groups that experienced different treatment methods. The researchers used a validated reading comprehension test which they administered before and after the intervention to collect their data. The study results found that the two groups showed no significant difference in their pre-test scores which showed that both groups had equal reading comprehension skills before the strategies started. The post-test results showed both groups made substantial reading comprehension progress because time-management techniques helped students learn to read and comprehend texts. The results showed that the two methods produced different levels of effectiveness which demonstrates the need to choose suitable methods that help maintain focus while people need to think actively. The study developed a Reading Toolkit for Teachers which contains structured reading comprehension improvement methods and instructional activities and assessment instruments based on study results. Time-management methods which include the Pomodoro Technique and Time-Blocking Method prove effective for enhancing reading comprehension according to the study findings which recommend using these techniques during reading lessons.